The constatation of the prosecutor’s role as dominus litis in the optimal evidentiary system based on ius constitutum for the achievement of legal objectives in indonesia - Triono Rahyudi; J. Ronald Mawuntu; Merry E. Kalalo; Herlyanty Y. A. Bawole (Scholar Center, 2026)
This abstract discusses the importance of strengthening the dominus litis principle within Indonesia’s criminal justice system. The research problem arises from the still limited role of prosecutors, who are only involved after the investigation is declared complete, resulting in the prosecutorial control function not operating optimally. This study aims to analyze the essence of the dominus litis principle in the existing criminal procedural law, the urgency of prosecutorial authority during the evidentiary stage, and the concept of strengthening the prosecutor’s role in the reform of the Criminal Procedure Code (KUHAP). The research employs a normative legal research method using statutory and conceptual approaches through the examination of primary and secondary legal materials. The findings indicate that the involvement of prosecutors from the early stages of criminal proceedings is necessary to ensure the quality of evidence, the integrity of law enforcement, and the achievement of justice-oriented legal objectives. The study further emphasizes that the dominus litis principle needs to be progressively reinterpreted by positioning prosecutors as substantive actors in the construction of criminal cases. Therefore, reform of the Criminal Procedure Code is an urgent necessity in order to establish a modern, integrative, and accountable criminal justice system.